PENINGKATAN POTENSI WISATA PANTAI INDAH POHE MELALUI PEMBUATAN PENANDA LOKASI DI KOTA GORONTALO - Syafriani; Abdi Gunawan Djafar; niniek Pratiwi (Politeknik Kebangsaan, 2025)
This community service project focuses on enhancing the potential of Pantai Indah Pohe, a prominent tourist destination in Gorontalo, through the creation of effective location signage. Despite its natural beauty, the lack of clear, informative signage has hindered the area's accessibility and awareness among visitors. The objective of this project is to design and implement location markers that not only guide tourists but also promote sustainable tourism practices. The rationale behind this initiative stems from the growing demand for tourism infrastructure that supports both local community development and environmental conservation. The project involves collaboration between the local government, community groups, and the Universitas Negeri Gorontalo's Building Architecture Department. The method used is a combination of field observation, community engagement, and practical design solutions, ensuring that the signage aligns with the local culture and environment. The results of the project include the successful installation of durable, environmentally friendly signage and an increase in local tourism awareness. This initiative contributes to the sustainable development of tourism in the area, fostering both economic growth and environmental preservation, while also strengthening community participation in the preservation of local heritage and natural resources.